Analisis Dampak Pembangunan Infrastruktur Terhadap Pertumbuhan Ekonomi Inklusif Provinsi Sumatera Utara : Institut Pertanian Bogor - Hendra Andy Mulia Panjaitan; Sri Mulatsih; Wiwiek Rindayati (JURNAL EKONOMI DAN KEBIJAKAN PEMBANGUNAN, 2019)
The development of infrastructures is an important aspect in economic growth. It is because the existence of a infrastructure cause good increasing economic growth, through creation of new jobs, as well as reducing the levels of poverty and increasig per capita income. Inclusive growth is an important part of sustainable economic growth as shown in a global agreement on Sustainable Development Goals (SDGs), where the economic growth that can generate equity, reduce poverty and unemployment, and encourage economic growth faster. Economic growth that can be create equality, reduction poverty and unemployment, as well as the push the growth of economy the more fast. This study conducted an analysis of the impact of infrastructure development on inclusive economic growth in North Sumatra Province. The parameter estimates used are two-stages least square (2SLS). The data used are 33 district / cities in North Sumatra Province in the 2013-2017 period. The results showed that the GRDP growth was not inclusive, because it could increase GINI in North Sumatra.